A taxonomic revision of Neodietrichia (Araneae: Linyphiidae), a rarely encountered but widespread spider taxon - Milne, Marc A.; O’neil, Caylie; Bertaux, James (Zootaxa, 2023)
The linyphiid spider Dietrichia hesperia was described from California in 1933 by Crosby and Bishop. The genus was renamed to Neodietrichia in 2008 by Özdikmen since Dietrichia was already occupied by a fossil bivalve. Until now, this rarely collected arboreal spider was the sole member of Neodietrichia. Herein we revise the genus by redescribing Neodietrichia hesperia (Crosby and Bishop, 1933), transferring Lophomma depressum (Emerton, 1882) to Neodietrichia as Neodietrichia depressum n. comb., and provide the first description of the female of this species.